2012
DOI: 10.1210/en.2012-1330
|View full text |Cite
|
Sign up to set email alerts
|

A Fall in Plasma Free Fatty Acid (FFA) Level Activates the Hypothalamic-Pituitary-Adrenal Axis Independent of Plasma Glucose: Evidence for Brain Sensing of Circulating FFA

Abstract: The brain responds to a fall in blood glucose by activating neuroendocrine mechanisms for its restoration. It is unclear whether the brain also responds to a fall in plasma free fatty acids (FFA) to activate mechanisms for its restoration. We examined whether lowering plasma FFA increases plasma corticosterone or catecholamine levels and, if so, whether the brain is involved in these responses. Plasma FFA levels were lowered in rats with three independent antilipolytic agents: nicotinic acid (NA), insulin, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 30 publications
4
15
0
Order By: Relevance
“…Additionally, higher plasma CORT levels and/or increased sensitivity to glucocorticoid actions have a significant impact on glucose and fatty acid homeostasis [43,44]. Results in mammals indicated that stress-induced circulating free fatty acid levels were altered by activation of the HPA axis [45,46]. In the present study, we found that isolation stress increased plasma NEFA levels significantly in layers but not broiler chicks, while plasma glucose levels were unchanged in both (Fig.…”
Section: Discussionsupporting
confidence: 48%
“…Additionally, higher plasma CORT levels and/or increased sensitivity to glucocorticoid actions have a significant impact on glucose and fatty acid homeostasis [43,44]. Results in mammals indicated that stress-induced circulating free fatty acid levels were altered by activation of the HPA axis [45,46]. In the present study, we found that isolation stress increased plasma NEFA levels significantly in layers but not broiler chicks, while plasma glucose levels were unchanged in both (Fig.…”
Section: Discussionsupporting
confidence: 48%
“…Indeed, plasma epinephrine levels significantly increase (about 2.5-fold) after oral ingestion of NiAc in fasting humans (31). In a rat study, FFA was acutely lowered in the fasting state either by NiAc, an A 1 adenosine receptor agonist, or by insulin in combination with glucose infusion to maintain euglycemia (32). In support of the above idea, increases in plasma adrenocorticotropic hormone and the lipolytic hormone corticosterone were attenuated with insulin/glucose (a situation somewhat akin to the fed state) compared with the other interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Blood, liver, and BB samples were taken 6 h after treatment, which was chosen since in previous studies in the same species that was the time period necessary to achieve changes in the FA-sensing mechanisms when levels of FA were increased (Librán-Pérez et al 2012, 2013b, 2014a. Initial concentrations of SDZ were selected based on the studies carried out previously in mammals (Cox et al 1997;Oh et al 2012), and then in preliminary studies (data not shown) we evaluated different SDZ doses. Since SDZ is known to reduce mean arterial pressure and heart rate at high doses (Cox et al 1997) we selected a dose (60 µg kg −1 ) that is able to lower levels of circulating FA without inducing any other alteration.…”
Section: Experimental Designmentioning
confidence: 99%
“…The treatment with SDZ WAG 994 (SDZ), a selective A1 adenosine receptor agonist that inhibits lipolysis (Jacobson and Gao 2006), has been used in mammals to experimentally induce decreased levels of FA, which are sensed in central areas through FA-sensing mechanisms (Le Foll et al 2009;Blouet and Schwartz 2010). The detection elicits counter-regulatory responses to restore FA levels, which have been associated with the activation of the hypothalamus-pituitary-adrenal (HPA) axis (Oh et al 2012(Oh et al , 2014. Thus, the enhanced lypolysis (especially in liver) induced by raised levels of circulating glucocorticoids would restore plasma FA levels (Oh et al 2012(Oh et al , 2014.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation